2011
DOI: 10.1097/tp.0b013e318215e742
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the Promise of Operational Tolerance in Clinical Transplantation

Abstract: Long-term acceptance of transplanted organs without requirement for indefinite immunosuppression remains the ultimate goal of transplant clinicians and scientists. This clinical state of allograft acceptance termed "operational tolerance" has been elusive in routine practice. However, there are published reports of recipients where immunosuppression has been discontinued, by intention or patient noncompliance, in which the outcome is a nondestructive immune response and normal function. The question now arises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 120 publications
0
21
0
Order By: Relevance
“…Problems of immunologic injury and long-term complications of immunosuppression (including drug toxicity; neoplasms; and/or infections) however remain formidable, such that efforts in the last decade have concentrated on development of less toxic immunosuppressive agents and attempts to induce tolerance of the graft by the host immune system. 1,2 While positive steps have been recorded, this field continues to be both challenging in the quest to achieve true tolerance and exciting in terms of emerging knowledge. The surgical pathologist plays a critical role as a member of the clinical team managing these transplant patients.…”
Section: Introductionmentioning
confidence: 98%
“…Problems of immunologic injury and long-term complications of immunosuppression (including drug toxicity; neoplasms; and/or infections) however remain formidable, such that efforts in the last decade have concentrated on development of less toxic immunosuppressive agents and attempts to induce tolerance of the graft by the host immune system. 1,2 While positive steps have been recorded, this field continues to be both challenging in the quest to achieve true tolerance and exciting in terms of emerging knowledge. The surgical pathologist plays a critical role as a member of the clinical team managing these transplant patients.…”
Section: Introductionmentioning
confidence: 98%
“…While bone grafting is most commonly recommended to treat oral bone deficiency (Chen & Jin 2010, Mao, et al 2006, Pellegrini, et al 2009), its use is restricted due to significant limitations, which include donor site morbidity, risk of infection, inappropriate synthetic architecture, and post-implantation failures (Alpdogan & van den Brink 2012, Becktor, et al 2002, Bishop, et al 2011, Blanco, et al 2005, Brunel, et al 2001, Chen & Jin 2010, Delloye, et al 2007, Rios, et al 2011, Spin-Neto, et al 2013, Spin-Neto, et al 2014, Waasdorp & Reynolds 2010). Alternatively, many studies have observed that growth factors, including demineralized bone matrix (DBM) and bone morphogenetic proteins (BMP), successfully enhance oral bone augmentation (Gruskin, et al 2012, Higuchi, et al 1999, Kim, et al 2014, Wallace, et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Safe, reliable strategies for the induction of full tolerance have not yet been developed [28]. However, during the study of achieving immune tolerance, methods to induce states of "partial tolerance" have been discovered; in these cases, lower-than-conventional amounts of ongoing pharmacologic immunosuppression are required to prevent rejection.…”
Section: Induction Of Tolerancementioning
confidence: 99%